Phylogenetic relationships in Kerkia and introgression between Hauffenia and Kerkia (Caenogastropoda: Hydrobiidae). (8th December 2016) - Rysiewska, Aleksandra; Prevorčnik, Simona; Osikowski, Artur; Hofman, Sebastian; Beran, Luboš; Falniowski, Andrzej
Abstract: Freshwater truncatelloidean gastropods include numerous minute cryptic species, displaying simple morphologies, all of which hampers their taxonomic research based on morphology. Phylogenetic relationships among all but one extant species of the genus Kerkia from five localities in Croatia and one in Slovenia were therefore analysed based on one mitochondrial ( cytochrome c oxidase subunit I ) and three nuclear markers ( 18S, 28S and H3 ). Kerkia kusceri (Bole, 1961 ), K. jadertina Kuščer, 1933, K. j. sinjana (Kuščer, 1933), and K. kareli Beran, Bodon et Cianfanelli, 2014, were collected from their type localities. Our analysis confirmed their distinctness, recovering two additional clades that may represent yet undescribed species from Croatia. Apart from Kerkia, Hauffenia media Bole, 1961, H. subpiscinalis (Kuščer, 1932) and H. erythropomatia (Hauffen, 1856) from Slovenia were analysed. Their distinctness together with the rejection of the eligibility for separate genus Erythropomatiana for the latter species was proven. Interestingly, its sequence divergence exceeded all previous estimates for species‐level divergence within the Truncatelloidea, implying a species‐level separation both for the COI and for nuclear loci. High p ‐distances for the COI /nuclear loci (0.128/0.027, respectively) confirmed also the uniqueness of both genera. A comparison of their COI sequences with the reference sequences of Alzoniella Giusti et Bodon, 1984, Avenionia Nicolas, 1882, Fissuria Boeters, 1981, and Agrafia Szarowska et Falniowski, 2011, has shown that Kerkia and Hauffenia are not sister clades. The most striking, however, was the apparent introgression of the ' Hauffenia ' mtDNA type from central Slovenia (cave Babja luknja) into two Kerkia clades from central (Ljubač) and southern (Podgrađe) Croatia, that are located 210 km and 360 km away, respectively. The introduced ' Hauffenia ' mtDNA type and the closest Hauffenia erythropomatia COI differed by 0.8%. Secondary loss of isolating mechanisms between phylogenetically distant organisms and the severe lack of information on distribution of these underground taxa were postulated as possible explanations of this interesting phenomenon. Abstract : Phylogenetic relationships among four species of Kerkia from five localities in Croatia and one in Slovenia, analyzed with one mitochondrial and three nuclear markers, confirmed their distinctness. There was introgression of the Hauffenia mtDNA from central Slovenia into two Kerkia clades from central and southern Croatia, located 210 and 360 km away, respectively. Secondary loss of isolating mechanisms between phylogenetically distant organisms and the severe lack of information on distribution of these underground taxa may explain this unusual phenomenon.